A new species of black fly with a yellow thorax in the genus Prosimulium (Diptera: Simuliidae) in Japan - Takaoka, Hiroyuki; Saito, Katsumi; Adler, Peter H.; Baba, Minoru (Magnolia Press, 2018)
A new species of black fly, Prosimulium kazukii, is described based on female, male and pupal specimens collected from central Honshu, Japan. It is placed in the Prosimulium magnum species-group, and is characterized in the female and male by yellow thoraces, and in the pupa by the frons and dorsal surface of the thorax without distinct tubercles. By these characters, it is distinguished from all four related species (P. apoina Ono, P. kalibaense Ono, P. sarurense Ono, and P. yezoense Shiraki) of the same species-group in Japan. The female of this new species was previously known as an aberrant form of P. yezoense.